RATIONAL USE AND MANAGEMENT OF PROTECTION ZONES OF HIGH-VOLTAGE POWER LINES: THE EXPERIENCE OF THE FERGANA VALLEY (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article deals with the issues of rational use of protection zones of high-voltage power lines (PTL) on the example of the Fergana region. Special attention is paid to the analysis of legal, environmental and economic aspects of land use in such zones. The data on the length and area of protected zones, their impact on agricultural and residential areas are presented. The use of satellite image illustrates the distribution of protective zones in the region, emphasizing the need for strict consideration of their boundaries in order to prevent legal and environmental conflicts. In conclusion, recommendations are proposed for optimizing the management of protected zones using GIS technologies and strengthening cadastral registration.